2016
DOI: 10.1111/jon.12395
|View full text |Cite
|
Sign up to set email alerts
|

Poststroke Cognitive Decline is Independent of Longitudinal Changes in Cerebral Hemodynamics Parameters

Abstract: Although hemodynamic parameters deteriorate in a considerable proportion of patients during first 3-6 months after a cerebrovascular event, cognitive decline appears to be an independent phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…The threshold for differentiating between high and low WMHL was set at 5 cm 3 (median value, 0.7% of WM volume, 0.27% of brain volume). Similar to previous studies [30][31][32][33] Gaussian random field theory with a threshold of p<0.05 37 . Similar to the survival analysis, the threshold for differentiating between high and low WMHL was 5 cm 3 .…”
Section: Discussionsupporting
confidence: 88%
“…The threshold for differentiating between high and low WMHL was set at 5 cm 3 (median value, 0.7% of WM volume, 0.27% of brain volume). Similar to previous studies [30][31][32][33] Gaussian random field theory with a threshold of p<0.05 37 . Similar to the survival analysis, the threshold for differentiating between high and low WMHL was 5 cm 3 .…”
Section: Discussionsupporting
confidence: 88%
“…The threshold for differentiating between high and low WMHL was set at 5 cm 3 (median value, 0.7% of WM volume, 0.27% of brain volume). Similar to previous studies ( Suministrado et al, 2017 ; Baracchini et al, 2012 ; Suzuki et al, 2015 ; Joana et al, 2013 ), a stable 2-point drop in MoCA (a drop that persists over the follow-up visits) was considered as the terminal event in the survival analysis and the time from baseline MoCA measurement to the visit where the 2-points drop was detected was considered as survival time. This was consistent with recommendations from our in-house clinical consultation.…”
Section: Methodsmentioning
confidence: 99%
“…The principal mechanisms involved are chronic hypoperfusion, microembolization and cerebrovascular reactivity impairment. Therefore, assessment of CVR may help identifying high-risk patients who may benefit from revascularization (Shroder et al 2019 ) Acute ischemic stroke The correlation between impairment of CVR and the occurrence of acute ischemic stroke in patients with severe internal carotid artery stenosis has been convincingly confirmed (Gur et al 1996 ; Silvestrini et al 1996 ; Silvestrini et al 2000 ; Markus and Cullinane 2001 ; Cheng et al 2012 ; Viticchi et al 2021 ) Alterations of hemodynamic factors and CVR have been related to the final infarct volume, unfavorable long-term outcome and most neurologic complications after acute stroke (Alvarez et al 2004 ) Cerebral hemodynamic parameters are progressively compromised according to stroke severity (Salinet et al 2019 ) In lacunar infarcts, the increase in PI has been correlated with impairment of executive functions (Sivakumar et al 2017 ) A recent pilot study and suggested that hemodynamic alterations may contribute at worsening cognitive performances transiently, during the first 3–6 months following acute subcortical ischemia (Suministrado et al 2017 ) Cerebral hemodynamic impairment plays a significant pathophysiological role in the acute phase of cerebral ischemia, and somehow predicts stroke severity, progression and long-term outcome …”
Section: Discussionmentioning
confidence: 99%
“…This may lead to vascular contraction and hypoperfusion, in turn causing functional alterations of connectivity within associative networks (Chi et al 2020 ). A recent pilot study, however, did not support such hypothesis, and suggested that hemodynamic alterations may contribute at worsening cognitive performances transiently, during the first 3–6 months following acute subcortical ischemia (Suministrado et al 2017 ).…”
Section: Cvr In Cerebrovascular Diseasesmentioning
confidence: 98%